Analysis of the Role of Village Owned Enterprises (BUMDes) in the Developmentand Empowerment of Cemba Village Communities, Enrekang Sub-District, Enrekang District - Smikdar Reskiawan; Alwiah sulaeman; Nugri Gugah Anugrayana; Asdir Muhammad (IECON: International Economics and Business Conference, 2023)
With the research title “Analysis of the Peren of village-owned enterprises (BUMDes) in the development and empowerment of the Cemba Village commuity, Enrekang sub-district, Enrekang district”. Advisor I Mr. Ruslang T. SE.,M.Si and Advisor II Mrs. Jumriani, SE., M.Si. Thesis on the economic development planning study program, faculty of Economics and Business, University of Muhammadiyah Parepare. This study aims to determine 1) This study aims to describe the role of BUMDes in village development in Cemba Village, Enrekang District, Enrekang Regency. 2) Describe the role of Bumdes in empowering rural communities in Cemba Village, Enrekang District, Enrekang Regency. This study uses a qualitative method with a descriptive approach that describes some of the findings of the data formulated in the form of words. The data collection techniques used are observation, interviews, and documentation. The data analysis technique uses word reduction, data presentation, and conclusion drawing. The results of this study are 1) the role of Bumdes in Cemba Village in Village Development, 2) Implementation of Bumdes in Village Development and Community Empowerment, 3) Lack of competent human resources in Bumdes, 4) People do not use BUMDES as a third party for economic recovery.